2012
DOI: 10.1161/strokeaha.112.653055
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Score (A 2 DS 2 ) to Predict Pneumonia in Acute Ischemic Stroke

Abstract: ; for the Berlin Stroke Register and the Stroke Register of Northwest Germany Background and Purpose-Poststroke pneumonia is a potentially preventable complication after stroke associated with poor outcome. We developed and externally validated a prognostic score for predicting risk of pneumonia after ischemic stroke. Methods-The prognostic score was developed based on clinical data routinely collected after admission from the Berlin Stroke Register, Germany. The association of demographics, comorbidities, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
163
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(197 citation statements)
references
References 40 publications
(29 reference statements)
10
163
1
11
Order By: Relevance
“…Findings of the study showed that smoking, alcohol intake, dysphagia, age, hemorrhagic type of stroke, and need for intubation were factors independently increased the risk for developing pneumonia. Age, dysphagia, hemorrhagic stroke, and need for intubation have all been previously reported as risk factors for stroke-associated pneumonia, [1,4,5,[9][10][11][12][13] which is consistent with our findings. However, this study identified another risk factor not yet reported in literature which is alcohol intake, but the data on the amount and duration of alcohol intake were not obtained.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Findings of the study showed that smoking, alcohol intake, dysphagia, age, hemorrhagic type of stroke, and need for intubation were factors independently increased the risk for developing pneumonia. Age, dysphagia, hemorrhagic stroke, and need for intubation have all been previously reported as risk factors for stroke-associated pneumonia, [1,4,5,[9][10][11][12][13] which is consistent with our findings. However, this study identified another risk factor not yet reported in literature which is alcohol intake, but the data on the amount and duration of alcohol intake were not obtained.…”
Section: Discussionsupporting
confidence: 93%
“…[1,6,9,13] In this study, the mean NIHSS for the cases is 19, while that for the controls is 11 with an overlap in the NIHSS scores between the two groups, suggesting statistically non-significant OR. Clinically, stroke severity can be classified using NIHSS scores as to mild (≤4), moderate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and severe (more than 15). Based on the mean scores, this study suggests that NIHSS scores differed in both groups clinically but did not attain statistical significance.…”
Section: Discussionmentioning
confidence: 47%
“…Calibration was assessed by performing the Hosmer-Lemeshow goodness-of-fit test and was graphically depicted in the plot of observed versus predicted SAP risk according to 10 deciles of predicted risk. Furthermore, we compared the discrimination of the AIS-APS and 3 prior scores, [25][26][27] with regard to in-hospital SAP after AIS. The AUROC and maximum Youden index were used to assess the discrimination of these scores for in-hospital SAP after AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is lacking risk stratification and precise therapeutic regimen of SAP. Sarah et al [2] carried out an assessment and analysis on multiple risk factors of SAP in 15 335 patients with acute ischemic stroke, and established the A2DS2 scoring tool. They found that the tool had excellent resolving power for prediction of SAP, and may be used in identification of patients at high risk and to guide preventive and management measures for pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early identification of patients at a high risk of SAP may help physicians to monitor the disease and prescribe proper treatment. A2DS2 scoring tool [2] is recognized as an effective method for predicting SAP. In this study, the A2DS2 scoring tool was used to evaluate the risk and prognosis of pneumonia in cerebral stroke patients treated in our department from 2009 to 2011.…”
Section: Introductionmentioning
confidence: 99%